Sintesis dan Karakterisasi Material Beton Hidrofobik dan Self Healing Berbasis Mikroorganisme - Yulia Maulida; Ratnawulan; Riri Jonuarti; Harman Amir (Postgraduate, University of Mataram, 2023)
The high water absorption of concrete causes the concrete to easily experience cracking and damage. One way to increase the durability of concrete is by adding microbes which can fill the micro cavities in the concrete with the resulting Calcium Carbonate (CaCO3) deposits. However, the weakness of using microorganisms is that they are unable to withstand high hydration heat. Therefore, by varying the temperature in this research, it is possible to determine the effect of the metabolism of the bacteria produced. This research was carried out to avoid damage by creating a hydrophobic and self-healing layer which helps increase the durability and strength of the concrete. The concrete sample made resembles a cube measuring 5 cm x 5 cm x 5 cm. The manufacturing materials are Portland cement, Otawa sand, distilled water and a mixture of E. coli bacteria. Heating was carried out using an oven at temperatures of 30, 60, 90, and 120 oC. Characterization testing was carried out using a Cpmreson machine, XRD and contact angle testing.